Contemporary nutrition issues and insights - Wardlaw, Gordon M. ([S.l.] : mcGraw Hill, 2003)
This book is organized into six parts that reflect the major topics typically covered in an introduction to the study of nutrition: Part One Nutrition: A Key To Health; Part Two The Energy-Yielding Nutrients and Alcohol; Part Three Vitamins and Minerals; Part Four Energy: Balance and Imbalance; Part Five Nutrition: A focus on Life Stages; Part Six Nutrition: Beyond the Nutrients. The Table of Contents also reflects the inclusion of two chapters not typically found in introductory textbooks: Chapter 7, Alcohol and Chapter 12, Eating Disorders. The expanded discussion of these topics is the result of feedback from instructors who felt it was important to provide their students with a thorough, balanced discussion of these relevant topics.
Keywords: nutrition,food science,vitamins,nutrient and alcohol